(untitled) (Eurasian Journal of Ecology, 2019)
In the article the ecological and biological features of a rare species Anthemis trotzkiana Claus growing under the conditions of the Aktobe region are identified. A biomorphological analysis of the species, studied in three populations, has been conducted; the species were divided into ecological types. In the populations studied, it has been determined that the life forms of the species according to I.G. Serebryakov do not apply to trees and shrubs. Among perennial herbaceous plant species, 55% from the 1st population, 63.1% from the 2nd population and 66.6% from the 3rd population are peculiar to the vegetation cover. It has been clarified that, according to K. Raunkier’s system, sprawling perennial hemicryptophytes prevail in the community of 3 populations. We found that, in terms of humidity, more than 50% of the composition of all species populations belong to mesoxerophytes. According to the adaptability to the ecological conditions of plant species’soil, obligate and optional calcephytescan be found.In the Anthemis trotzkiana Claus studied in all populations,8 obligate calcephytes were found:Anabasis cretacea Pall.,Achillea nobilis L., Anthemis trotzkiana Claus, Crambe tataria Sebeok., Linaria cretacea Fisch. ex Spreng., Zygophyllum pinnatum, Limonium cretaceum Tscherkasova, Echinops meyeri (DC) Iljin.In populations, 6 species (30%) were found in the chalky soil mountains of Akshatau, 4 species (21%) in the Bestau chalky mountain chains (21%) and 5 species (23.8%) in the chalky soils of Ishkaragantau. Also on the territories of the populations, optional calcephytes that can grow on other substrateshave been identified; in the 1st population, 14 species adapted (70%), in the 2nd population – 15 species (79%) and in the 3rd population – 16 species (76.2%). Key words: Anthemis trotzkiana Claus, population, plant life forms, ecological types, сalcephyte.